Identification and analysis of aromatic components in Piper sarmentosum Roxb. from Meru Betiri National Park - Hariani, Sulifah Aprilya; Novenda, Ika Lia; Mudakir, Imam; Asyiah, Iis Nur; Pujiastuti, Pujiastuti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Piper sarmentosum Roxb or known as mana Karuk is an aromatic plant that has extraordinary potential, namely as a mucus expectorant, its roots are efficacious as a ureter and overcome gallstones. This plant is also used as an asthma drug, a cure for skin diseases such as tinea versicolor, stomach pain, malaria medicine, relieve bone pain and dental pain. The components of aromatic chemical compounds in the leaves and fruits from Meru Betiri National Park (MBNP) have not been identified. This study aimed to identify and analyze the aromatic components of P. sarmentosum leaves and fruits from MBNP using SPME-GCMS. The research method is laboratory research. The research samples and research materials were the leaves and fruit of the P. sarmentosum plant taken in MBNP. The SPME-GCMS tool is used in research to identify and analyze aromatic compounds. The research instrument used was an identification and analysis sheet of aromatic compounds from the P. sarmentosum plant. The data analysis technique uses the SPME-GCMS test. The results of the study showed that there were 46 volatile compounds found in the leaves, while in the fruit there were 29 volatile compounds. The main aromatic compound groups in the leaves and fruits of P. sarmentosum are terpenes, namely monoterpene. The other components consist of organic benzene compounds. P. sarmentosum Roxb. has 46 aromatic compounds in the leaves and 29 other aromatic compounds found in the fruit. Furthermore, research results must be tested in more depth regarding biological activity and mechanism of action through the best methods so that they can be recommended as new drug innovations in society.